A Semantic Analysis of Figurative Language in The Soundtrack of The Phantom of The Opera - Aulia Monica Tambunan; Bernieke Anggita Ristia Damanik (Yayasan Bayt Shufiya Nusantara, 2025)
This study aims to examine the use of figurative language in The Phantom of the Opera by identifying its types and meanings through a semantic lens. Employing a qualitative descriptive design with a library research approach, the analysis focuses on selected dialogues and song lyrics from the film. The findings reveal five dominant types of figurative language—symbol, metonymy, personification, metaphor, and hyperbole. These figurative elements not only enhance the emotional depth of the characters but also enrich the artistic and narrative quality of the musical. The study concludes that figurative language plays a significant role in conveying complex emotions and underlying themes, thereby fostering a deeper appreciation of nonliteral meaning in musical storytelling.